1989
DOI: 10.1002/jso.2930420505
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Therapy for Advanced Prostatic Carcinoma

Abstract: Since the work of Huggins and Hodges, hormonal therapy, i.e., orchiectomy or estrogens, has been the gold standard of treatment for patients with advanced adenocarcinoma of the prostate. Recently, many new drugs have been introduced in the hope of achieving a beneficial response as compared with hormonal therapy, while avoiding some of the adverse effects. Various newer agents are reviewed. It appears that while these agents may be attractive secondary to specific effects, they do not appear to offer any survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…This was based on the finding that enzymes converting testosterone to DHT and dihydroepiandrostenedione to androstenedione were upregulated to a greater extent than the other enzymes in the synthesis pathway (32,33). However, it has also been demonstrated that an adrenalectomy paired with ADT does not limit CaP progression, suggesting limited involvement of adrenal precursors (34,35). Overall, it appears that adrenal precursors are not the only source of ligand for AR activation, and de novo androgen synthesis is likely required to provide sufficient ligand for maintaining this pathway in CRPC cells.…”
Section: De Novo Androgen Synthesis In Castration-resistant Prostate mentioning
confidence: 97%
“…This was based on the finding that enzymes converting testosterone to DHT and dihydroepiandrostenedione to androstenedione were upregulated to a greater extent than the other enzymes in the synthesis pathway (32,33). However, it has also been demonstrated that an adrenalectomy paired with ADT does not limit CaP progression, suggesting limited involvement of adrenal precursors (34,35). Overall, it appears that adrenal precursors are not the only source of ligand for AR activation, and de novo androgen synthesis is likely required to provide sufficient ligand for maintaining this pathway in CRPC cells.…”
Section: De Novo Androgen Synthesis In Castration-resistant Prostate mentioning
confidence: 97%
“…Relative contra-indications to the procedure have included patients with bleeding diathesis, immunocompromise, and chronic infection. For many years, bilateral orchiectomy was held as the gold stand¬ ard for hormonal therapy of advanced prostate cancer (Herbst 1941, Seftel et al 1989). Nonsurgical forms of castration were also discovered during the 1940s with the introduction of estrogen therapy (Daneshgari & Crawford 1993).…”
Section: Introductionmentioning
confidence: 99%